Adoption of lentil varieties in Bangladesh: An expert elicitation approach (Bangladesh Journal of Agricultural Research, 2018)
The study was undertaken to find out variety wise adoption rate of lentil in Bangladesh through expert elicitation procedure. Many varieties have been developed by BARI and BINA but in details of varietal information and adoption information database was not developed which is very important and valuable for the scientist and policy planner. From all over the Bangladesh, 12 experts was invited to share their valuable knowledge and experience on lentil cultivation and adoption in the country. The average age of the experts were 51 yrs and average experience on lentil adoption was 21 yrs. The lentil expert informed that 16 major varieties are adopted by the farmers in the recent year (2013-14). Among those varieties, BARI Masur-6 covered highest cultivated area (54,642 ha) which shared 30.04% of total lentil cultivated area. BARI Masur-4, BARI Masur-3 and BARI Masur-5 ranked 2nd, 3rd and 4th position according to the share of cultivated area covered. The seed production information showed that BADC the only lentil seed producer supplied 2151 mt of lentil seed in the year 2009-2013.The adoption of variety BARI Masur-6 increased due to its high yield attribute. The another variety BARI Masur-4 and BARI Masur-3 adoption increased due to its high yield, resistant to rust disease attributes which showed increasing adoption path among the expert. Satisfying higher demand for lentil consumption and ensuring food security through providing alternative to winter crops are the major concerning issue of the policy planner and the scientist. To ensure nutrition security in the country, it is very important to encourage and support the farmers to grow more lentil through providing improved cultivation technology to the farmers.Bangladesh J. Agril. Res. 43(1): 159-168, March 2018